2008
DOI: 10.1097/shk.0b013e318158125b
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ovine Model of Methicillin-Resistant Staphylococcus Aureus-Induced Pneumonia and Sepsis

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA)-related pneumonia and/or sepsis are a frequent serious menace. The aim of the study was to establish a standardized and reproducible model of MRSA-induced septic pneumonia to evaluate new therapies. Sheep were operatively prepared for chronic study. After 5 days' recovery, tracheostomy was performed under anesthesia, and smoke injury was induced by inhalation of cotton smoke (48 breaths, <40 degrees C). Methicillin-resistant S. aureus (AW6) (approximately 2.5x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 28 publications
4
56
0
Order By: Relevance
“…This model is characterized by a more severe vascular leak syndrome than the P. aeruginosa pneumonia-induced severe sepsis model studied here (46). Consistent with the observations that we reporting here, we showed that POV was superior to AVP at stabilizing MAP and SVRI and at reducing vascular leak, as shown by a reduction in fluid requirements, cumulative fluid balance, and thoracic cavity and abdominal cavity fluid accumulation, as well as by an attenuation of the decrease in plasma total protein concentration and plasma oncotic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…This model is characterized by a more severe vascular leak syndrome than the P. aeruginosa pneumonia-induced severe sepsis model studied here (46). Consistent with the observations that we reporting here, we showed that POV was superior to AVP at stabilizing MAP and SVRI and at reducing vascular leak, as shown by a reduction in fluid requirements, cumulative fluid balance, and thoracic cavity and abdominal cavity fluid accumulation, as well as by an attenuation of the decrease in plasma total protein concentration and plasma oncotic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The ovine model of methicillin resistant staphylococcus aureus pneumonia-induced sepsis has been described in detail by Enkhbaatar and colleagues (11). In brief, 24 female sheep were fasted for 24 h before the experiment began, but had free access to water.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the present study was designed as a prospective, randomized, controlled laboratory experiment to elucidate the effects of these treatment strategies on neutrophil activation, nitrosative stress, and markers of vascular dysfunction, namely angiopoietin-2 and VEGF, as well as on cardiovascular and pulmonary function. The study hypothesis was tested in an established ovine two-hit model of severe sepsis resulting from methicillin resistant staphyloccocus aureus-induced pneumonia after smoke inhalation injury (11,15). …”
mentioning
confidence: 99%
“…However, if there have been few experimental studies on the development of small animal models of MRSA-induced pneumonia, there have been even fewer using large animal models of MRSA. Nevertheless, it is important to point out the relevance of the study of ENKHBAATAR et al [22], using an ovine model of MRSA-induced pneumonia and sepsis that closely mimics hyperdynamic human sepsis. Authors established a standardised and reproducible model of MRSA-induced septic pneumonia by instillation of S. aureus, with and without smoke injury induced by inhalation of cotton smoke.…”
Section: Large Animal Models Of Mrsa-induced Pneumoniamentioning
confidence: 99%